A SCIENCE PROGRAM FOR THE DISADVANTAGED CHILD. - Webster, John W. (Science Education)
The article looks into the science program for disadvantaged children. The author points out that it is important for teachers to: (1) make a thorough examination of their attitudes concerning such children; and (2) make a careful assessment of their own biases, prejudices and expectations of such children. Significantly, popular beliefs such that disadvantaged children are non-verbal and disinterested in education must be addressed. School programs that are developed must not force middle class values on the children. The author contends that elementary science is an excellent medium for motivating and working with the special problems of disadvantaged children. The author recommends that significant considerations must be placed on the quality of learning experiences than on the quantity of the materials covered.